Appropriately Upset? A Methodological Framework for Tracing the Emotion Norms of the Transatlantic Security Community - Koschut, Simon (2018)
Emotions have been found to underpin the moral hierarchy of values and beliefs within and among groups by restraining undesirable attitudes and behavior. As such, emotions serve as potential indicators for analyzing whether or not certain norms are still deemed relevant. As Jon Mercer puts it: “One way to test for the presence of norms is to look for emotion”. While the literature in International Relations (IR) generally accepts the emotional underpinnings of norms, there has been strikingly little elaboration of appropriate methods and criteria for studying the link between emotion and norms in IR. In this contribution, I suggest that socialization processes in a security community involve the internalization of appropriate rules of emotional expression or, in short, emotion norms. I propose that emotion norms can be historically traced via the emotional vocabulary and expressive rules derived from the production of texts. To do this, I searched for documents and treaties that serve as canonical texts for the collective self-conception and self-image of the transatlantic security community. As I hope to show, in these texts one can find substantial evidence of emotion norms, which designates these documents as ‘emotional landmarks’ that embody the emotional construction of the transatlantic emotional (security) community.